(untitled) (Economics and region, 2020)
The main business processes of a tourist enterprise aimed at creating a tourist product are considered. It is defined the essence of the business process of a tourist enterprise and highlighted its properties. The business model is considered and formed, which is divided into four main levels. Several methods have been identified for business process modeling, based on a structured and objectively oriented approach to modeling. The business processes of tourist product realization are structured.